Peptide Occurring in Enterobacteriaceae Triggers Streptococcus pneumoniae Cell Death - Nasher, Fauzy; Kwun, Min Jung; Croucher, Nicholas J.; Heller, Manfred; Hathaway, Lucy J. (Frontiers in Cellular and Infection Microbiology, 2019)
Non-encapsulated Streptococcus pneumoniae often possess two genes, aliB-like ORF 1 and aliB-like ORF 2, in place of capsule genes. AliB-like ORF 1 is thought to encode a substrate binding protein of an ABC transporter which binds peptide SETTFGRDFN, found in 50S ribosomal subunit protein L4 of Enterobacteriaceae. Here, we investigated the effect of binding of AliB-like ORF 1 peptide on the transcriptome and proteome of non-encapsulated pneumococci. We found upregulation of gene expression of a metacaspase and a gene encoding N-acetylmuramoyl-L-alanine amidase, both of which are proposed to be involved in programmed cell death in prokaryotic cells. Proteome profiling indicated upregulation of transcriptional regulators and downregulation of metabolism-associated genes. Exposure to the peptide specifically triggered death in pneumococci which express AliB-like ORF 1, with the bacteria having an apoptotic appearance by electron microscopy. We propose that binding of the AliB-like ORF 1 peptide ligand by the pneumococcus signals a challenging environment with hostile bacterial species leading to death of a proportion of the pneumococcal population.